Sosialisasi Budidaya Lebah Madu Tanpa Sengat (Stingless Bee) Dan Manfaatnya - Ummu Harmain; Jef Rudiantho Saragih; Marulam MT Simarmata; Muldri P J Pasaribu (Jurnal Pengabdian Masyarakat Sapangambei Manoktok Hitei, 2022)
There are honey-producing bees that have a sting and do not have a sting (stingless bee). The last type of bee is still rarely known to the public. To introduce these bees, socialization needs to be done. Socialization activities use the method of extension and dissemination of science and technology. This activity explains the conditions of the honey market in Indonesia, types of honey bees, determinants of production, benefits and techniques for harvesting honey and stingless bee pollen. During the activity, the participants enthusiastically listened to the material and played an active role, especially during the discussion and question and answer sessions regarding honey harvesting and pollen processing techniques. For the practice of stingless honey bee cultivation, bee colonies of the Heterotrigona itama species are given to the target community group